Spanish organic law of religious freedom of November 5, 1980 - Ryguła, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The subject of the analysis is the legal regulations regarding religious freedom in Spain. The first part is dedicated to article 16 of the Constitution in which the Spanish legislative body placed the declaration of the separation of the Church from the State and guaranteed religious freedom. The second part is a discussion on the regulations given in the Organic Law of Religious Freedom of November 5, 1980. It is development and precise explanation of the constitutional guarantees contained in article 16. The analysis is structured in the following order: a) an objective and subjective scope of the statutory guarantees regarding religious freedom in Spain; b) protection of religious law by the State; c) legal identity, autonomy, inner structure of the religious groups; d) juridical instruments for implementing cooperation between state authorities and religious groups in Spain.